เทคโนโลยีในกระเป๋ากับรอยร้าวทางสังคม: บทเรียนจากภัยดิจิทัล - เสนามาตย์, พ.ต.ท.ชนันท์ธิพัฒน์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
In the digital era, mobile phones have evolved into primary communication instruments that permeate every dimension of human existence, encompassing communication, professional activities, education, and unrestricted access to information. While such technology facilitates societal development, unethical usage has precipitated the phenomenon of 'social fragmentation' that continues to expand progressively. This article analyzes the impacts of mobile phone usage that lead to digital threats, comprising sexual blackmail through private digital media, the dissemination of disinformation that undermines public credibility, and political information leakage that affects international relations.The analysis is grounded in major sociological frameworks: Structural Functionalism, which explains the role of technology within the social system and the consequences of role deviation; Conflict Theory, which examines how technology can be instrumentalized to create power leverage and conflict; and Symbolic Interactionism, which addresses how meanings are constructed and interpreted through digital media. Findings indicate that mobile phones are a “double-edged sword,” functioning as both a tool for generating economic, social, and cultural value and as a conduit for harm at the individual, community, and structural levels. The speed and breadth of communication through online networks allow such threats to escalate rapidly and produce wide-ranging impacts in a short period of time. Policy recommendations emphasize the integration of updated and enforceable legal measures, the cultivation of a digital culture rooted in ethics, the enhancement of media literacy skills, and the promotion of collaboration between governments, the private sector, civil society, and platform providers. These measures are essential for building societal resilience and mitigating the severity of social fractures in the digital age.